1975
DOI: 10.1139/e75-118
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical Studies of North African Cenozoic Volcanic Areas: III. Garian, Libya

Abstract: Paleomagnetic and K/Ar whole rock absolute age data are described for material from the Garian area of Libya, centered at 13°E, 32°N. Within-unit cleaned paleomagnetic directions from the essentially unaltered lavas are very well defined and can almost certainly be taken as reliable measurements of the geomagnetic field direction during the initial cooling of each flow. However, the distributions of mean direction, from which the effect of repeated sampling of the field at one time has been removed, does not s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…(b) Some poles included in previous compilations have been re-dated. The Libyan basalts, initially thought to be Oligocene have now been re-dated as Pliocene (Ade-Hall et al 1975).…”
Section: A N a P W P F O R A F R I C Amentioning
confidence: 99%
“…(b) Some poles included in previous compilations have been re-dated. The Libyan basalts, initially thought to be Oligocene have now been re-dated as Pliocene (Ade-Hall et al 1975).…”
Section: A N a P W P F O R A F R I C Amentioning
confidence: 99%
“…Different forms Figure 1 for location). Black patches = volcanic fields <30 Ma; colored circles = loci of volcanic samples described and analyzed in this study; labeled boxes = names of individual volcanic fields with ranges of radiometric dates taken from Ade-Hall et al (1975a), Bardintzeff et al (2012), Busrewil and Esson (1991), Cvetković et al (2010), Deniel et al (2015), Jurák (1978), Masoud (2014), Radivojević et al (2015), and Schult and Soffel (1973); dotted line = outline of Sirt Basin taken from Abdunaser and McCaffrey (2015). of sample screening are used to mitigate the effects of crystal fractionation, of lithospheric contamination, and of source heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…The doubts regarding the high basalt ages of PlCCOLI, expressed in the paper of ADE-HALL et al (1975), have to be confirmed. Unfortunately however, the determinations of ADE-HALL et al (1975) cover not the variety of the most common volcanic types of the Jebel Nefusa.…”
Section: Age Relationshipsmentioning
confidence: 91%
“…The recent age determinations of ADE-HALL et al (1975) yield only very young ages of flood basalts. The doubts regarding the high basalt ages of PlCCOLI, expressed in the paper of ADE-HALL et al (1975), have to be confirmed.…”
Section: Age Relationshipsmentioning
confidence: 98%
See 1 more Smart Citation